Factors Affecting Job Satisfaction of General Practitioners at Level III Hospital Brawijaya Surabaya - Pratama, Willy Danis; Syaodih, Erliany; Handayani, Nining (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Improving the quality of services in an effort to provide public services is the main concern of the government, especially optimal health services to ensure decent living conditions for all people. Doctors as human resources who have a very important role in hospitals so they need management attention to manage/nurture so that they can carry out their work well so that they can contribute to the performance/progress of the hospital. The purpose of this study is to find out the management factors that affect the job satisfaction of doctors at Level III Hospital Brawijaya Surabaya. The population of this study is 42 doctors. The sampling technique used is the sample to be conducted is the total population. The type of research used by the author is a qualitative approach that is descriptive analysis. Statistical instruments in a quantitative way with univariate, bivariate and multivariate methods, using the chi square test and logistic regression test using the enter method. Based on the results of the study, there was an influence of clarity of medical services, suitability of medical services, leadership decision-making, leadership support, leadership responsiveness, workplace cleanliness, workplace comfort, completeness of infrastructure, and promotion opportunities on doctors' job satisfaction by 36.3% while the remaining 63.7% (100% - 36.3%). There are joint effects on doctors' job satisfaction Management factors which include clarity of medical services, workplace cleanliness and workplace comfort, affect together on doctors' job satisfaction Management factors that most affect doctors' job satisfaction at Level III Hospital Brawijaya Surabaya are the clarity of medical services.